2008
DOI: 10.1200/jco.2008.17.7428
|View full text |Cite
|
Sign up to set email alerts
|

Late Congestive Heart Failure After Hematopoietic Cell Transplantation

Abstract: Purpose To examine the independent roles of pre–hematopoietic cell transplantation (HCT) therapeutic exposures, transplantation-related conditioning, and comorbidities (pre- and post-HCT) in the development of late congestive heart failure (CHF) after HCT. Methods This was a nested case-control design. Individuals with late CHF (diagnosed ≥ 1 year after HCT) were identified from a cohort of 2,938 1+ year survivors who underwent transplantation at City of Hope National Medical Center, Duarte, CA. This cohort fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(104 citation statements)
references
References 37 publications
7
95
1
1
Order By: Relevance
“…[21][22][23][24] However, a larger, retrospective cohort study showed no statistically significant difference in the incidence of congestive heart failure among patients with acute GVHD, those with a history of chronic GVHD and Cardiac dysfunction in the chronic phase of HCT M Nishimoto et al those with active GVHD. 25 Uderzo et al 13 report similar findings in childhood HCT. This study was limited by its retrospective, nonrandomized design and small study population.…”
Section: Discussionsupporting
confidence: 71%
“…[21][22][23][24] However, a larger, retrospective cohort study showed no statistically significant difference in the incidence of congestive heart failure among patients with acute GVHD, those with a history of chronic GVHD and Cardiac dysfunction in the chronic phase of HCT M Nishimoto et al those with active GVHD. 25 Uderzo et al 13 report similar findings in childhood HCT. This study was limited by its retrospective, nonrandomized design and small study population.…”
Section: Discussionsupporting
confidence: 71%
“…In general, patients who survive 5 years after transplantation without relapse are considered to be cured of disease. However, there is increasing evidence of the deleterious long-term health consequences of ASCT, including increased rates of treatment-related myelodysplasia/leukaemia, secondary solid tumours, and cardiac and pulmonary toxicity (Pedersen-Bjergaard et al, 2000;Bhatia et al, 2005;Brown et al, 2005;Kalaycio et al, 2006a,b;Armenian et al, 2008). In a comprehensive study of late mortality in survivors of ASCT, Bhatia et al (2005) revealed that mortality exceeds those of the general population until 10 years after ASCT in certain subgroups of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who have undergone ASCT for relapsed or refractory DLBCL are at increased risk of mortality well beyond 5 years, which is the time point that has been widely accepted a surrogate for long-term survival (Pedersen-Bjergaard et al, 2000;Bhatia et al, 2005;Brown et al, 2005;Kalaycio et al, 2006a,b;Armenian et al, 2008). Whether deaths occurring after 5 years are due to disease relapse mortality (RM) or nonrelapse mortality (NRM) is poorly studied.…”
Section: Research Paper First Published Online 13 January 2011mentioning
confidence: 99%
“…Further, preceding Ն 2 comorbidities were associated with increased post-HCT congestive heart failure. 63 A study from MDACC found increased incidence of post-HCT cardiac toxicities if patients had one of seven preceding cardiac comorbidities. 64 Clearly, additional investigations are required to better predict and prevent organ toxicity based on preexisting multiple comorbidities.…”
Section: Impacts Of Multiple Comorbidities On Post-hct Organ Toxicitiesmentioning
confidence: 99%